FOOTBALL TRAINING CENTER IN TEGAL REGENCY WITH A SUSTAINABLE ARCHITECTURE APPROACH - Panji Zulfan Nirwana; Andi Purnomo; Eko Budi Santoso; Wiwit Setyowati (Universitas Negeri Semarang, 2025)
Football is one of the most popular sports in Indonesia and the world today. The interest of the community is very excited even to the corners of the region. Football knows no age, gender, or social status. From children to the elderly, men and women, from businessmen to ordinary villagers, all love it. Sports areas, especially the Football Training Center have an important role in the development of quality football athletes. This research aims to design and develop a sustainable sports area that focuses on the efficient use of natural resources. The methodology used involved field surveys, environmental analysis, and an in-depth understanding of the needs and demands of the Football Training Center users. A sustainable approach was applied in the design by considering aspects such as energy efficiency, use of environmentally friendly materials, utilization of renewable energy, wise water management, and creation of a healthy environment. The result of this design includes various facilities that support quality football training, such as training fields, fitness centers, classrooms, and treatment and recovery facilities. These facilities were designed with user comfort, energy efficiency, and reduced environmental impact in mind. In addition, measures such as the use of environmentally friendly building materials, efficient waste treatment, and utilization of solar energy for lighting and water heating were implemented in this design. A wastewater treatment system was also built to reduce negative impacts on the surrounding environment. With this sustainable architecture approach, the Football Training Center is expected to be an example in the development of a sustainable sports area. The application of sustainable practices in the design of sports areas can provide long-term benefits for both users, the surrounding community, and the natural environment as a whole.